Decreased serum osmolality promotes ductus arteriosus constriction. (4th September 2014) - Aoki, Rika; Yokoyama, Utako; Ichikawa, Yasuhiro; Taguri, Masataka; Kumagaya, Shun; Ishiwata, Ryo; Yanai, Chiharu; Fujita, Shujiro; Umemura, Masanari; Fujita, Takayuki; Okumura, Satoshi; Sato, Motohiko; et al.
Abstract: Aims: At birth, dynamic changes occur in serum components and haemodynamics, such as closure of the ductus arteriosus (DA). A previous study demonstrated that, in full-term human neonates, serum osmolality decreased transiently after birth, but recovered over the next few days. However, the significance of this transient decrease in osmolality has never been addressed. The objective of the present study was to examine the role of changes in serum osmolality after birth in DA closure. Methods and results: We found that rats exhibited a similar transient hypoosmolality after birth. Hypotonic stimulation induced constriction of DA rings and increased Ca 2+ transient in DA smooth muscle cells, but not in the aorta. The hypoosmotic sensor transient receptor potential melastatin 3 (TRPM3) was highly expressed in the rat DA, and TRPM3 silencing abolished the Ca 2+ response to hypoosmolality. Pregnenolone sulfate stimulation of TRPM3 induced rat DA constriction ex vivo and in vivo. Furthermore, hyper tonic fluid injection impaired rat DA closure. In humans, neonatal serum hypoosmolality was observed in relatively mature preterm infants (≥28 weeks). In extremely preterm infants (<28 weeks), however, this hypoosmolality was absent. Instead, a rapid increase in osmolality occurred thereafter. Such an increase was greater, in particular, among patent DA (PDA) patients. Conclusions: A transient decrease in serum osmolality may promote DA closure during the first few days of life. Adjusting serum osmolality to proper levels might help to prevent the onset of PDA, improving the therapeutic outcome in extremely preterm infants.